56y-712=34y-136

Combine 56 and y.

5y6-712=34y-136

Combine 34 and y.

5y6-712=3y4-136

Subtract 3y4 from both sides of the equation.

5y6-712-3y4=-136

To write 5y6 as a fraction with a common denominator, multiply by 22.

5y6⋅22-3y4-712=-136

To write -3y4 as a fraction with a common denominator, multiply by 33.

5y6⋅22-3y4⋅33-712=-136

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply 5y6 and 22.

5y⋅26⋅2-3y4⋅33-712=-136

Multiply 6 by 2.

5y⋅212-3y4⋅33-712=-136

Multiply 3y4 and 33.

5y⋅212-3y⋅34⋅3-712=-136

Multiply 4 by 3.

5y⋅212-3y⋅312-712=-136

5y⋅212-3y⋅312-712=-136

Combine the numerators over the common denominator.

5y⋅2-3y⋅312-712=-136

Combine the numerators over the common denominator.

5y⋅2-3y⋅3-712=-136

Simplify the numerator.

Multiply 2 by 5.

10y-3y⋅3-712=-136

Multiply 3 by -3.

10y-9y-712=-136

Subtract 9y from 10y.

y-712=-136

y-712=-136

y-712=-136

Multiply both sides of the equation by 12.

12⋅y-712=12⋅(-136)

Cancel the common factor of 12.

Cancel the common factor.

12⋅y-712=12⋅(-136)

Rewrite the expression.

y-7=12⋅(-136)

y-7=12⋅(-136)

Simplify 12⋅(-136).

Cancel the common factor of 6.

Move the leading negative in -136 into the numerator.

y-7=12⋅-136

Factor 6 out of 12.

y-7=6(2)⋅-136

Cancel the common factor.

y-7=6⋅2⋅-136

Rewrite the expression.

y-7=2⋅-13

y-7=2⋅-13

Multiply 2 by -13.

y-7=-26

y-7=-26

y-7=-26

Add 7 to both sides of the equation.

y=-26+7

Add -26 and 7.

y=-19

y=-19

Solve for y 5/6y-7/12=3/4y-13/6